2017
DOI: 10.2147/ott.s138956
|View full text |Cite
|
Sign up to set email alerts
|

<em>TERT-CLPTM1</em> locus polymorphism (rs401681) is associated with the prognosis of hepatocellular carcinoma

Abstract: Telomere length is associated with the development of hepatocellular carcinoma (HCC), and recent studies have focused on the genetic alteration or polymorphism in telomere-maintaining genes. We examined the clinicopathologic and prognostic value of rs401681 polymorphism, located in the TERT-CLPTM1L locus, in HCC. The relationship between rs401681 variants and telomere length was also analyzed in 156 HCC patients. The rs401681 polymorphism had the following genotype frequencies: C/C in 51.3% of the samples, C/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
(42 reference statements)
2
4
0
Order By: Relevance
“…proteinatlas.org). High expression of CLPTM1L and CLPTM1L expression-controlling polymorphisms 23 in tumors are associated with poor prognosis as described here and previously in 24 . The function of CLPTM1L is best understood in the context of antiapoptotic activity 2,[10][11][12]16,17,25 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…proteinatlas.org). High expression of CLPTM1L and CLPTM1L expression-controlling polymorphisms 23 in tumors are associated with poor prognosis as described here and previously in 24 . The function of CLPTM1L is best understood in the context of antiapoptotic activity 2,[10][11][12]16,17,25 .…”
Section: Discussionsupporting
confidence: 77%
“…Data collected and annotated by the Human Protein Atlas also demonstrates high CLPTM1L expression in a variety of cancers including ovarian serous adenocarcinoma with no expression in normal ovary tissue or normal fallopian epithelium (available from http://www.proteinatlas.org ). High expression of CLPTM1L and CLPTM1L expression-controlling polymorphisms 23 in tumors are associated with poor prognosis as described here and previously in 24 . The function of CLPTM1L is best understood in the context of anti-apoptotic activity 2 , 10 – 12 , 16 , 17 , 25 .…”
Section: Discussionsupporting
confidence: 65%
“…The TERT gene is thought to be involved in an apoptotic response, and its level of expression affects the susceptibility of cancer cell lines to anticancer drugs. Whole-genome association studies have identified the TERT gene rs401681 as one of the most significant cancer-associated SNPs [ 29 ]. A study made by Ma and co-authors discusses the relationship between TERTp mutation and telomere length.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, RFA is the prime treatment option for late-stage HCC, particularly for patients with cirrhosis or for those whose liver functional reserve precludes radiotherapy. 32 However, HCC can aggressively and rapidly recur after RFA. 32 To protect nontumor liver tissue, we cannot indefi-nitely increase the ablation temperature or power during RFA treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 32 However, HCC can aggressively and rapidly recur after RFA. 32 To protect nontumor liver tissue, we cannot indefi-nitely increase the ablation temperature or power during RFA treatment. On the other hand, RFA may induce cellular stress and pathological changes in HCC cells.…”
Section: Discussionmentioning
confidence: 99%